Effectiveness of Borage plus syrup on COVID-19 patients in intensive care units - Hashemian, Seyed MohammadReza; Mortaz, Esmaeil; Shafigh, Navid; Ziaie, Shadi; Jamaati, Hamidreza; Hasheminik, Morteza; Jamalinik, Mehdi; Erfani, Raziyeh; Khoundabi, Batoul; Dezfuli, Neda K.; Varahram, Mohammad; Ahmadi, Shahrzad; et al. (Frontiers in Nutrition, 2022)
Abstract Introduction: COVID-19 (coronovirus disease-2019) still causes a high rate of death globally with no definite curative treatment described. The traditional plant Borage (Borago officinalis L.) is a good source of gamma-linolenic (GLA). We hypothesized that Borage plus syrup (BPS) would be beneficial in severe COVID-19 patients within an intensice care unit (ICU) setting. Methods: A pilot single centre, randomized trial with no placebo was undertaken. 60 PCR-positive severe COVID-19 participants admitted to ICU from June 2020- Dec 2020 at Masih Daneshvari Hospital Tehran-Iran gave informed consent. The participants were randomly assigned to either Borage Plus Syrup (BPS, 5ml per diem for 4 days) (n=30) or standard care (IFN- and favipiravir) as a control group (n=30). Pao2/Fio2, serum ferritin, CRP, bilirubin, IL-6, TNF-α, ALT, AST, PCT and serum IL-8 was measured upon admission and on release. Results: All the measured parameters decreased significantly with BPS treatment except ALT. In the control group, most parameters significantly improved apart from ALT, AST and PCT. In addition, the suppression of serum TNF levels in the BPS group was greater than that seen in the control group (P≤0.05). Moreover, the length of ICU stay was significantly lower in the BPS group compared with the control group (P≤0.05). Conclusion: Our study shows that addition of BPS to the standard treatment regime of COVID-19 patients in ICU improved outcomes and reduced the length of ICU treatment. Natural products could be considered as new approaches for reducting the harmful consequences of COVID-19.